2002
DOI: 10.1002/1521-4141(200212)32:12<3699::aid-immu3699>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Emerging principles for the design of promiscuous HLA-DR-restricted peptides: an example from the major bee venom allergen

Abstract: Mechanisms underlying successful immunotherapy of allergic patients operate at the level of CD4+ helper T cells. T cell epitopes from allergens may thus constitute interesting molecules for immunotherapy, provided they are efficient for all patients and are not recognized by IgE. In an attempt to define such peptides for allergy to bee venom, we have investigated the capacity ofpeptides encompassing the sequence of the major bee venom allergen to stimulate PBMC from allergic patients and to react specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Its recombinant form produced in Escherichia coli was found as allergenic as the wild-type molecule (Forster et al 1995) in contrast to the denatured protein or internal fragments Texier et al 2002). Therefore, IgE epitopes appear to be contained mainly in the polypeptide side chains (and not in the glycosylated moieties) and to be conformational .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Its recombinant form produced in Escherichia coli was found as allergenic as the wild-type molecule (Forster et al 1995) in contrast to the denatured protein or internal fragments Texier et al 2002). Therefore, IgE epitopes appear to be contained mainly in the polypeptide side chains (and not in the glycosylated moieties) and to be conformational .…”
Section: Discussionmentioning
confidence: 98%
“…As the B cell epitopes of Api m 1 were essentially of the conformational type Texier et al 2002), we investigated the secondary and tertiary structure of the molecules by CD and fluorescence spectroscopy. We observed that Api wt and Api mut shared a similar content of secondary structure (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations